Empowerment of rural women farmers and food production in Rathnapura district in Sri Lanka: a household level analysis - Rathnachandra, S D D (Applied Studies in Agribusiness and Commerce, 2020)
Women empowerment and gender equity are two significant aspects of the sustainable development of a country. As Sri Lanka is on the way towards sustainable development, this study was conducted to assess the situation of women farmers’ empowerment and food production in Rathnapura district of the country. A sample of 300 women farmers was randomly selected for the study, from two selected Divisional Secretariat (DS) of Rathnapura district. Data was collected from a field survey using a pre-tested, self-administered questionnaire survey from April to July 2019. Empowerment was analyzed using the empowerment framework used by RAHMAN AND NAOZORE in 2007 in the study of “Women Empowerment through Participation in Aquaculture” with necessary modifications. Data analysis was conducted using descriptive statistics, correlation analysis and multiple linear regression analysis. Results revealed that majority of the women farmers were middle aged, married and had children. Furthermore, most of them had education up to secondary level. While average family size was four, average farm size was 1.25 acres. They had around 16 years of farming experience. The average monthly income of them was 25,000.00 LKR whereas 20% of it was from agriculture. The main sources of empowerment of women farmers were the Agrarian Service Center (55%) followed by village organizations/societies (30%) and microfinance institutions (26%). Furthermore, women empowerment index was 0.65. It is a moderate level of empowerment. However, there were women farmers under three categories of empowerment levels: low empowerment (4.1%), medium empowerment (58.5%) and high empowerment (36.1%). Out of the socio-economic factors; age, education, family size, land size, number of training programs participated, monthly income, experience in agriculture and number of organizations participated, education and number of training programs attended had significant and positive effect for the empowerment. Accessibility of credit facilities and agricultural extension program participation showed that there was a considerable impact on food production rather than the cultivable land size and utilization of modern farming technologies for food production. Therefore, proving of timely important agricultural education and training programs, enhance awareness level of modern farming technology utilization, better micro finance programs and agricultural credit facilities will be able to enhance the empowerment level of the women farmers of this area furthermore. JEL CODE: Q01, Q12